Consumer's Electronic Word-of-Mouth Adoption: The Trust Transfer Perspective. Issue 4 (2nd October 2019) - Lee, Jieun; Hong, Ilyoo B.
ABSTRACT: Consumers' trust in the source of an online review message is largely determined by the consumers' trustworthiness beliefs about the source that can potentially influence their willingness to engage in a transaction. While extant research examined consumer trust in a message source (i.e., a reviewer), little attention has been paid to the role of trust transfer within the review platform in forming source trustworthiness perceptions in the electronic word-of-mouth (e-WOM) context; source trustworthiness refers to the extent to which the composer of a review message deserves trust. It is the primary aim of this research to understand how trust transfer between related targets affects a consumer's assessment of online reviews. We empirically examined consumers' e-WOM adoption mechanism from the trust transfer perspective. We constructed a conceptual model based on the elaboration likelihood model and the trust transfer theory, and we tested the model using data collected from an online survey conducted on TripAdvisor.com. The findings revealed that trust is transferred from the review site to the community of reviewers, and then to a specific reviewer, but not directly from the review site to a specific reviewer. It was also found that consumer trust in a specific reviewer and review helpfulness both contribute to review adoption. This study offers some implications from these findings.